Linguistic Harmony and National Integration: Policy Perspectives 2047 - Basavaraj Bilagi (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
In today’s rapidly globalizing world, linguistic diversity often presents challenges to national cohesion and integration. This research paper examines the intricate relationship between linguistic harmony and national integration, with a particular focus on policy perspectives that could be adopted by nations by the year 2047. We explore the historical context, relevant theories, and current policies surrounding language use in various regions, emphasizing the implications for national identity and social unity. Through a comprehensive literature review, we identify best practices and recommend strategies that may foster linguistic harmony and, in turn, enhance national integration. The paper concludes by highlighting the essential role of policymakers in shaping inclusive language policies to achieve societal harmony. Linguistic harmony is a critical element in fostering national integration, particularly in multilingual nations. This paper explores the relationship between linguistic unity and national cohesion in the context of current and future policy directions, particularly through 2047. As countries strive for integration amidst diversity, ensuring linguistic harmony emerges as a key consideration. This study highlights the significance of language policies in fostering national unity, identifying challenges and proposing strategic frameworks to enhance linguistic integration for a harmonious society.